Prediksi Kejadian Demam Berdarah Dengue di Kecamatan Papar Kabupaten Kediri Tahun 2016–2021 - marlik marlik; Ridha fajar Lutfianawati; ngadino ngadino (ASPIRATOR - Journal of Vector-borne Disease Studies, 2022)
Abstract. Dengue Hemorrhagic Fever is a health problem in Indonesia. Papar is included in the area with the highest number of dengue casesThe purpose of the study was to find out the prediction of dengue hemorrhagic fever incidence in papar subdistrict, Kediri regency based on dengue fever cases. This type of research is quantitative with retrospective. Data analysis using ARIMA time series model. The best ARIMA model is ARIMA (1, 0, 0) with the equation Yt = 0.9974 Y t- 1 + α t. The MSE value on the prediction is 28,41. The predicted results in January will be an increase in cases then can do PE and fogging. In July with the lowest number of cases can take PSN and 3M plus action. Abstrak. Demam Berdarah Dengue merupakan masalah kesehatan di Indonesia. Kecamatan Papar, Kabupaten Kediri termasuk dalam daerah dengan jumlah kasus DBD tertinggi. Tujuan penelitian untuk mengetahui prediksi kejadian DBD di wilayah Kecamatan Papar, Kabupaten Kediri. Jenis penelitian ini adalah kuantitatif dengan metode retrospektif. Analisis data menggunakan time series model ARIMA. Model ARIMA terbaik yaitu ARIMA (1, 0, 0) dengan persamaan Yt = 0.9974 Yt - 1 + α t . Nilai MSE pada prediksi adalah 28,41. Hasil prediksi pada bulan Januari akan terjadi kenaikan kasus maka dapat melakukan PE dan fogging. Pada bulan Juli dengan jumlah kasus terendah dapat melakukan tindakan PSN dan 3M Plus.